2012
DOI: 10.1155/2012/858306
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Predictors of Peanut, Tree Nut, Fish, Shellfish, and Sesame Allergy in Canada

Abstract: Background. Studies suggest that the rising prevalence of food allergy during recent decades may have stabilized. Although genetics undoubtedly contribute to the emergence of food allergy, it is likely that other factors play a crucial role in mediating such short-term changes. Objective. To identify potential demographic predictors of food allergies. Methods. We performed a cross-Canada, random telephone survey. Criteria for food allergy were self-report of convincing symptoms and/or physician diagnosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…Similar to previous studies by our group and others, high income was associated with higher odds of food allergy [1,9] . In line with previous findings by our group, high education was associated with tree nut allergy [9] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies by our group and others, high income was associated with higher odds of food allergy [1,9] . In line with previous findings by our group, high education was associated with tree nut allergy [9] .…”
Section: Discussionsupporting
confidence: 91%
“…In a previous population-based telephone survey performed between May 2008 and March 2009, Canadians of lower income and education and New Canadians were underrepresented [7,9,10] . Hence, to ensure these vulnerable populations were included in our subsequent 2010/2011 study, we used a targeted sampling strategy that included regions containing the highest proportions of those of lower income and education, immigrants, and those of self-reporting Aboriginal identity.…”
Section: Study Samplementioning
confidence: 98%
“…Together, these studies reported on 11 relationships between SEP and different allergies, of which nine results in seven studies pointed towards a higher prevalence for people of higher SEP [51][52][53][54][55][56][57]. One study found no relationship between SEP and doctor-diagnosed atopic eczema in Japanese children [58].…”
Section: Association Between Allergic Diseases and Sepmentioning
confidence: 99%
“…These findings support other observations showing the relative importance of socioeconomic and atopic factors in childhood food allergies. 22,[25][26][27] Early life feeding practices, such as exclusive breastfeeding duration and timing of introduction of complementary foods in relation to important dietary milestones at 4 or 6 months of age, were not significantly associated with overall pFA. However, children who were exclusively breastfed for at least 4 months had borderline significantly lower odds of developing a new pFA compared with those who were not exclusively breastfed.…”
Section: Discussionmentioning
confidence: 93%